2009
DOI: 10.1080/10903120802706252
|View full text |Cite
|
Sign up to set email alerts
|

Pilot Test of the SALT Mass Casualty Triage System

Abstract: The SALT mass casualty triage system can be applied quickly in the field and appears to be safe, as measured by a low undertriage rate. There was, however, significant overtriage. Further refinement is needed, and effect on patient outcomes needs to be evaluated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
1
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 16 publications
2
33
1
3
Order By: Relevance
“…15 One smaller study employing virtual-reality simulation reported triage accuracy of 70% when SALT was used, 8 while two higher fidelity, mock-disaster simulations incorporating patient actors and manikins found EMS responders triaged accurately using SALT in 78.8% and 81.0% of cases. 13,14 The PCP trainees in this present study were able to triage 85.9% of the paper-based clinical scenarios accurately, suggesting EMS trainees with limited experience can utilize SALT accurately. Moreover, these results further support the notion that SALT and START triage accuracies are comparable.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…15 One smaller study employing virtual-reality simulation reported triage accuracy of 70% when SALT was used, 8 while two higher fidelity, mock-disaster simulations incorporating patient actors and manikins found EMS responders triaged accurately using SALT in 78.8% and 81.0% of cases. 13,14 The PCP trainees in this present study were able to triage 85.9% of the paper-based clinical scenarios accurately, suggesting EMS trainees with limited experience can utilize SALT accurately. Moreover, these results further support the notion that SALT and START triage accuracies are comparable.…”
Section: Discussionmentioning
confidence: 86%
“…Results published by Cone et al revealed paramedics using SALT overtriaged and under-triaged 13.5% and 3.8% of cases from a liveaction, mock MCI, respectively. 13 However, a similar, yet larger, SALT triage study involving over 214 patient encounters from 73 triage officers reported an opposing trend, where 8% of cases were over-triaged and 11% were under-triaged. 14 More recently, Cone et al reported triage errors resulting from a small virtual-reality MCI simulation.…”
Section: Discussionmentioning
confidence: 94%
“…Limited research has been conducted to identify the most effective method to learn SALT triage and assess an EMS provider's ability to use SALT triage. 3,4 A systemwide protocol change provided a unique opportunity to assess the introduction of SALT triage to a large, urban EMS agency. The three specific goals of this study were to measure EMS providers' understanding of SALT triage after an initial 20-minute lecture, evaluate their ability to accurately triage hypothetical victims of an MCI, and then reassess their knowledge of SALT triage and triage accuracy four months later.…”
Section: Introductionmentioning
confidence: 99%
“…Perhaps the two most commonly known techniques are START (simple triage and rapid treatment) 44 and SALT (sort-assess-lifesaving interventions-treatment/transport). 45,46 Some authors have proposed triage methodologies to be utilized in CBRN events. 47 Regardless of the technique that is used for triage, EMS providers are often called upon to make the determination of patients who should have priority and where in the health care system these patients should be transferred to for definitive care.…”
Section: Triagementioning
confidence: 99%